Therapeutic influence of Mozart's Sonata K448 on the attenuation of aversive memories and fear memory recall to sound stimuli in male mice (Research, Society and Development, 2024)
This study aimed to analyze the influence of Mozart's Sonata K448 on the process of recalling aversive memories to sound stimuli in male mice. Twelve pregnant female mice of the C57BL/6J strain were used, divided into three groups: the Mozart Group, exposed to Sonata K448; the Ambient Group, exposed to ambient sound; and the Control Group, also exposed to ambient sound. The male offspring were kept with their mothers until the 30th day of life and, after weaning, continued sound exposure until the 81st day. The process included habituation and conditioning with foot shocks associated with sound stimuli, followed by an Extinction Test over 12 consecutive days, where the mice were placed in the experimental chamber without receiving shocks. The behavioral analysis of the mice focused on freezing as a measure of memory for extinction. No significant differences were observed between the Mozart, Ambient, and Control groups in the aversive memory recall test. The average freezing values were also similar across groups, suggesting the absence of an effect of Sonata K448 on the modulation of fear memory recall. We conclude that, although Mozart's Sonata K448 did not show significant effects on fear memory recall, music remains a promising field for cognitive and emotional modulation. Future studies should explore different musical genres, exposure times, and combined interventions to elucidate the therapeutic potential of music in the recall of traumatic memories and mental health.